Anti-Performative Religious Authority in Algorithmic Culture: Rethinking Legitimacy through Inner Piety in the Digital Preaching of Gus Baha - Lia Hilyatul Masrifah; Robby Aditya Putra (Universitas Negeri Yogyakarta, 2026)
Digital media have changed how religious authority works by making visibility and engagement more important. Many studies in digital religion suggest that legitimacy depends on being visible in algorithms and presenting oneself strategically. This study questions that idea by looking at a different kind of religious authority that resists performative norms. I used an interpretive qualitative approach to analyze 30 sermon recordings from YouTube, published between February and December 2025, and 700 audience comments from various channels, including both official and informal community accounts. The analysis focused on how piety, authority, and authenticity are discussed and negotiated in digital religious spaces. For Gus Baha, authority came from inner piety, such as intention, ethical reasoning, and reflective understanding, and from keeping a clear distance from performative displays. Audience comments indicated that this non-performative approach appealed to listeners tired of moralistic, visibility-focused religious messages. They valued intellectual depth, humility, and emotional support over algorithmic popularity. This article introduces the idea of anti-performative religious authority and explains how it differs from authenticity, symbolic authority, and charismatic authority. The findings show that visibility is not required for religious legitimacy in algorithmic culture. The study also offers a framework for comparing digital religious figures, platforms, and communication contexts.